Contraindications to performing nasal allergen challenge - Chełmińska, Marta; Chełmiński, Konrad (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Contraindications to performing nasal allergen challenge are divided into absolute (health- or life-threatening, e.g. anaphylactic shock in anamnesis) and relative (may interrupt provocation test, e.g. nose deformation). It is necessary to consider every contraindication to the proper sequence of nasal provocation test.